Thrombelastographic hypercoagulability and antiplatelet therapy after coronary artery bypass surgery (TEG-CABG trial): a randomized controlled trial. (17th November 2017) - Rafiq, Sulman; Johansson, Pär I.; Kofoed, Klaus F.; Lund, Jens T.; Olsen, Peter S.; Bentsen, Simon; Steinbrüchel, Daniel A.
Abstract: A hypercoagulable state has, in observational studies, been associated with increased risk of thromboembolic events. The aim of this trial was to study whether dual antiplatelet therapy (DAPT) with clopidogrel in addition to aspirin could reduce the rate of graft occlusions, thromboembolic events, and death compared to aspirin monotherapy in hypercoagulable patients undergoing coronary artery bypass surgery. A total of 1683 patients were screened for eligibility, among which 165 patients were randomized and 133 patients underwent multislice computed tomography scan to evaluate their grafts. Thrombelastography (TEG) and multiplate aggregometry were performed before and after surgery, and again at three months follow up. TEG hypercoagulability was defined as the maximum amplitude above 69 mm. At three months follow up, 17 out of 66 (25.7%) DAPT patients and 15 of 67 (22.4%) aspirin patients had significant graft stenosis or occlusions ( p = 0.839). Saphenous vein grafts (SVGs) were stenosed or occluded in 15 (22.7%) patients in the DAPT group and 7 (10.4%) in the aspirin group ( p = 0.167). Thromboembolic events and death after the second postoperative day (when clopidogrel was started) were numerically, but not statistically, lower in the DAPT group, 3 (3.8%) vs. 8 (9.9%), p = 0.211. In univariate logistic regression analysis, only postoperative day 4 platelet response to aspirin measured with multiplate was correlated with graft occlusion, OR 1.020 [1.002–1.039], p = 0.033. This is the first trial to test the hypothesis of intensified antiplatelet therapy in hypercoagulable patients. Due to the low enrollment and high loss to follow up, our results can only be viewed as hypothesis generating. We found a high rate of graft occlusions in this patient population. Our results were not suggestive of that DAPT improved saphenous vein graft patency. A trend was observed in patients on DAPT toward fewer MI and deaths. Postoperative response to aspirin therapy was found to be associated with early SVG occlusion.